Evaluasi Peranan Anggaran Biaya Operasional sebagai Alat Pengendalian Manajemen (Studi Kasus pada PD Lima Motor Garut) - Christalia Sarah; Etti Ernita Sembiring (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
The purpose of this study was to determine and evaluate the role of the operational cost budget as a management control tool in the company. The research was conducted at PD Lima Motor Garut located on Jl. Raya Ciledug 190 RT 04/15, Garut. The results of this study are expected to increase knowledge and insight regarding the plan and realization of the operational cost budget as a management control tool at PD Lima Motor Garut. In addition, it can be a reference and consideration, as well as a reference to be used as material for further research. The research method used is a qualitative and descriptive method, where this study provides evaluation results from the results of interviews and documentation. The preparation of the operational cost budget for PD Lima Motor Garut begins with a negotiation process and ends with revising the budget for the following month. The budgeting method used is A Posteriori. Unexpected costs incurred by the company become one of the factors in preparing the budget. From the results of the study found a large variance in the months in 2019 and 2020. The results of this study are expected to be able to find out that the operational cost budget realized in the company has been effective or not, so an evaluation is needed to be able to correct any errors so that the plan and realization of the budgeted costs operational control as management control at PD Lima Motor Garut becomes more effective.